Unveiling Organic Electrode Materials in Aqueous Zinc-Ion Batteries: From Structural Design to Electrochemical Performance - Li, Dujuan; Guo, Yuxuan; Zhang, Chenxing; Chen, Xianhe; Zhang, Weisheng; Mei, Shilin; Yao, Chang‑Jiang (Nano-Micro Letters, 2024)
Aqueous zinc-ion batteries (AZIBs) are one of the most compelling alternatives of lithium-ion batteries due to their inherent safety and economics viability. In response to the growing demand for green and sustainable energy storage solutions, organic electrodes with the scalability from inexpensive starting materials and potential for biodegradation after use have become a prominent choice for AZIBs. Despite gratifying progresses of organic molecules with electrochemical performance in AZIBs, the research is still in infancy and hampered by certain issues due to the underlying complex electrochemistry. Strategies for designing organic electrode materials for AZIBs with high specific capacity and long cycling life are discussed in detail in this review. Specifically, we put emphasis on the unique electrochemistry of different redox-active structures to provide in-depth understanding of their working mechanisms. In addition, we highlight the importance of molecular size/dimension regarding their profound impact on electrochemical performances. Finally, challenges and perspectives are discussed from the developing point of view for future AZIBs. We hope to provide a valuable evaluation on organic electrode materials for AZIBs in our context and give inspiration for the rational design of high-performance AZIBs. Highlights: 1 A comprehensive introduction into organic cathode materials for aqueous zinc-ion batteries with specific focus on their structural–property relationship based on the variations in composition, geometry, and molecular size. 2 For each representative organic cathode, the unique electrochemistry has been discussed to provide insight into the underlying working mechanism. 3 Summarized pros and cons of different organic cathodes and outlined challenges plus future research directions.